Managing in the modern corporation the intensification of managerial work in the USA, UK and Japan - Hassard, John 1953- (Cambridge University Press, 2009)
In recent years, widespread organisational change in large corporations has almost invariably led to work intensification and increased stress for managers. Managing in the Modern Corporation explains how and why large companies have changed their organisational structures and philosophies, focusing in particular on how these changes affect the careers of middle managers. Based on in-depth interviews with over two hundred middle and senior managers working in large corporations in the USA, UK and Japan, it shows how the working lives of managers have been subjected to major disruption, involving work intensification and reduced opportunities for career progression. Furthermore, it argues that such widespread overwork and poor treatment of highly skilled and highly motivated staff has created a major international problem that must be addressed. The book presents a range of solutions to this important problem, suggesting that there are possibilities for saner, less brutal organisational environments